2023
DOI: 10.1007/s10649-022-10198-6
|View full text |Cite
|
Sign up to set email alerts
|

The relation between attitudes towards mathematics and dropout from university mathematics—the mediating role of satisfaction and achievement

Abstract: The transition from school to university mathematics is a challenging process for many students, which is reflected in high dropout rates during the first year at university. Using mediation analysis, we want to shed light on the role of students’ attitudes towards mathematics—especially their interest in mathematics and their mathematical self-concept—for early dropout and investigate the underlying mechanisms for the relations between attitudes and dropout. Informed by frameworks of person-environment-fit an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…The relations, as it is stated in the introduction, are then accepted by the results obtained as evidenced in studies such as those conducted by Xiao and Sun (2021) . Geisler et al (2023) also highlight the existence of relationships between attitudes toward mathematics and the academic achievement variable. Orbach et al (2019) also find inverse correlations between components of the math anxiety and academic performance variables.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The relations, as it is stated in the introduction, are then accepted by the results obtained as evidenced in studies such as those conducted by Xiao and Sun (2021) . Geisler et al (2023) also highlight the existence of relationships between attitudes toward mathematics and the academic achievement variable. Orbach et al (2019) also find inverse correlations between components of the math anxiety and academic performance variables.…”
Section: Discussionmentioning
confidence: 87%
“… Czocher et al (2020) proposed the training of self-efficacy and competence through mathematical modeling in university students, indicating the importance of an intervention to improve the construction of such self-efficacy. Along the same lines, another recent study highlights the importance of mathematics attitudes such as academic interest and self-concept and aspects such as degree of satisfaction and perceived achievement given their influence on the dropout rate during the first university years ( Geisler et al, 2023 ). Czocher et al (2020) found in first-year undergraduate students at a German university in some mathematics major (mathematics program and teacher education program) aged 17–33 years, using a gender-balanced sample, that attitudes toward mathematics such as mathematical interest and mathematical self-concept correlated inversely with the risk of academic dropout; to be specific, satisfaction was a mediating variable for both academic interest and academic self-concept.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…When we talk about attitudes toward mathematics we are somehow referring to the affective component of the construct (Geisler et al, 2023) that Emmioğlu and Çapa-Aydın (2012, p. 95) define as a "multidimensional construct that stands for students' learned predispositions to respond positively or negatively with regard to statistics. " It is necessary not to neglect this non-cognitive component so relevant to the teaching/learning process in Mathematics and Statistics (García-Suárez et al, 2023;Spencer et al, 2023).…”
Section: Introductionmentioning
confidence: 99%